(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2018)
The idea that the Dubai Government via its public sector institutions can and needs manage itself strategically, in a similar manner to any well-performing private sector organisation, has been translated into practically across government departments and authorities. This study is intended as contribution to knowledge production that will also fill a gap in literature on the salient and fundamental factors that enabled Dubais post-colonial state to be become agile, innovative and responsive to the growing size and scope of activities undertaken by Dubai and by extension the UAEs public sector institutions. On the basis of documentary analysis and observation, the conclusion has been arrived that a multiplicity of factors and initiatives such as strategic planning, innovation and technological advancement, leveraging of political leadership and hiring the finest minds from the global pool of transnational bureaucrats with the view to transfer skills and efficiently run public institutions.